Cost-effectiveness analysis of anidulafungin for the treatment of candidaemia and other forms of invasive candidiasis. Issue 1 (December 2015) - Auzinger, Georg; Playford, E.; Graham, Christopher; Knox, Hediyyih; Weinstein, David; Kantecki, Michal; Schlamm, Haran; Charbonneau, Claudie
Abstract Background Candidaemia and other forms of invasive candidiasis (C/IC) in the intensive care unit are challenging conditions that are associated with high rates of mortality. New guidelines from the European Society for Clinical Microbiology and Infectious Diseases strongly recommend echinocandins for the first-line treatment of C/IC. Here, a cost-effectiveness model was developed from the United Kingdom perspective to examine the costs and outcomes of antifungal treatment for C/IC based on the European Society for Clinical Microbiology and Infectious Diseases guidelines. Methods Costs and treatment outcomes with the echinocandin anidulafungin were compared with those for caspofungin, micafungin and fluconazole. The model included non-neutropenic patients aged ≥16 years with confirmed C/IC who were receiving intravenous first-line treatment. Patients were categorised as either a clinical success or failure (patients with persistent/breakthrough infection); successfully treated patients switched to oral therapy, while patients categorised as clinical failures switched to a different antifungal class. Other inputs were all-cause mortality at 6 weeks, costs of treatment-related adverse events and other medical resource utilisation costs. Resource use was derived from the published literature and from discussion with clinical experts. Drug-acquisition/administration costs were taken from standard United Kingdom costing sources. Results The model indicated that first-line anidulafungin could be considered cost-effective versus fluconazole (incremental cost-effectiveness ratio £813 per life-year gained) for the treatment of C/IC. Anidulafungin was cost-saving versus caspofungin and micafungin due to lower total costs and a higher rate of survival combined with a higher probability of clinical success. Discussion European Society for Clinical Microbiology and Infectious Diseases guidelines recommend echinocandins for the first-line treatment of C/IC; our model indicated that anidulafungin marries clinical effectiveness and cost-effectiveness. Conclusions From the United Kingdom perspective, anidulafungin was cost-effective compared with fluconazole for the treatment of C/IC and was cost-saving versus the other echinocandins.